Serving library users during a pandemic: the case of Karlstad University Library, Sweden (Journal of EAHIL, 2020)
During March 2020, all Swedish universities moved their teaching to an online environment due to the Covid-19 outbreak. Karlstad University Library in Sweden made a number of changes in order to reduce the spread of infection while at the same time maintaining a high level of library services to its users. Opening hours were drastically reduced. All study spaces were closed. Most of the staff were working from home. A new virtual reference desk via Zoom was launched to increase the library office hours. Since things happened fast, the internal staff training was done while at the same time providing the new reference service to the users. Some initial mistakes were made but in general, this ‘learn-as-you-go method’ worked surprisingly well.